Las retahílas como estrategia para la pronunciación en los niños del subnivel 2 de la Unidad Educativa Dr. “Gabriel García Moreno”, Cantón Guano - Pilco Gualoto, Deysi Maribel (2025)
The present research entitled the chants as a strategy for pronunciation in children of sublevel 2 at the Educational Unit Dr. “Gabriel García Moreno”, canton Guano. The general objective was to determine the importance of the use of chants, in order to support that pronunciation is the ability to verbalize the sounds of words in a clear and understandable way, especially in early education where children are in full growth of their vocabulary, which is essential for optimal development of their effective communication, Methodologically, the research contains a qualitative approach, with a non-experimental design, it has a bibliographic type of research because it was based on a compilation of information in reliable sources such as web pages, international and national university repositories and relevant academic articles. It is field research because it was carried out at the place where the facts took place. An observation technique was used to obtain contextualized information on the study phenomenon, for which an observation sheet was used based on the objective set and thus to understand the relationship between the two study variables, for the research we worked with a population of 25 children aged 4 to 5 years. Consequently, the procedure for the analysis and interpretation of the data obtained was reached, where it was possible to access their respective discussion, for which graphs and tables were used to indicate the results, which showed that the teacher does not apply chants constantly to teach the children, since there is a notable group that is in the process of having a correct pronunciation.